Breaking ground: Women and men’s preferences in animal breeding practices in Somaliland - Marshall, Karen (International Livestock Research Institute, 2016)
Interview with Karen Marshall (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684